Building a~sustainable and transferable sulphur emission free BSR - Gunnar Prause; Eunice O. Olaniyi (Sustainability Management Forum, 2020)
The maritime industry is getting much attention owing to the current energy and climate crises. There are increasing discussions on sustainable maritime transport across the globe especially after the successful implementation of the sulphur regulations in the Baltic Sea Region (BSR). The world is now getting ready for the 2020 global sulphur cap suggesting that the energy transition outlook in the maritime sector is becoming clearer and there is no going back.Still, global energy consumption is growing at an alarming rate, and all hands must remain on deck to avert possible world crises. There are still questions related to clean shipping, waste management, clean fuel, decarbonisation of fuel and greenhouse associated with global warming. What are the expected hurdles of a~complete transition to a~complete clean maritime transport industry? Can the world achieve total integration of this policy to contribute to environmental protection?The study investigates the effect of both public and private cost of environmental governance in the maritime sector and evaluates the budding orchestration of green/clean shipping initiatives to activate regulatory policies using the Sulphur Emission Control Area (SECA) regulation in the Baltic state region, its state of the art, coordination and cost. The study further addresses the gaps in the present and future development of regulation compliance focussing on their design, monitoring and control to meet the global outlook for the 2020 global sulphur cap.
Keywords: 650; Clean shipping; 2020 Global sulphur cap; DRY; Sustainability; Regulations